Oncocytic changes in pleomorphic adenoma: Report of a rare case - Kaur, Milanjeet (Indian J Dent, 2015)
Pleomorphic adenoma is the most common benign salivary gland tumor, accounting for almost three-fourths of all such tumors. Cells with oncocytic change are a common finding in salivary glands and in salivary gland tumors. When found within pleomorphic adenomas, cells with oncocytic changes may be perceived as evidence of malignancy, and lead to a misdiagnosis of carcinoma ex-pleomorphic adenoma. A case of pleomorphic adenoma arising de novo in the minor salivary glands with oncocytic changes is discussed here.